International Journal of Behavioral Nutrition and Physical Activity - Davison, Kirsten; Wood, Lesley; Jago, Russell; Cerin, Ester; Collins, Clare
International Journal of Behavioral Nutrition and Physical Activity (IJBNPA) is an open access, peer-reviewed journal offering high quality articles, rapid publication and wide diffusion in the public domain. IJBNPA is devoted to furthering the understanding of the behavioral aspects of diet and physical activity and is unique in its inclusion of multiple levels of analysis, including populations, groups and individuals and its inclusion of epidemiology, and behavioral, theoretical and measurement research areas.  IJBNPA prioritises research based on randomised controlled trials (RCTs), systematic reviews (with or without meta-analyses, as appropriate), and observational studies. IJBNPA will also review other study designs such as strong or ground-breaking methodological papers, rigorous qualitative studies, debate papers and commentaries. IJBNPA publishes pilot studies only in exceptional circumstances and it does not publish protocol papers or letters to the editors.